Comparison of the effect of the abdominal hysterectomy on female sexual function - Gabor Reyes, Iván (2015)
OBJETIVE: To compare the effect of abdominal hysterectomy type on female sexual function. MATERIALS AND METHODS: prospective descriptive study, according to the design 'only after', held at the Regional Hospital of Trujillo, Peru, in which 54 women undergoing total abdominal hysterectomy (HAT) and 54 women who underwent subtotal hysterectomy (HAST ) for benign disease between January 2001 and December 2003; They were randomly selected to answer a questionnaire that evaluates their sexual function (FSFI). The proportions of dysfunction scores each of the domains of sexual function were determined, as well. Comparisons were made using the chi-square test, z-test of proportions and the test 't'. RESULTS: The proportion of sexual dysfunction in patients undergoing high as (40.7%) was lower than in those undergoing HAT (48.1%), with no statistically significant difference (p> 0.05), and there are also no relationship between the variables. The average orgasm domains (4. 16 ± 1.28 vs. 4.66 ± 1.34) and satisfaction (4.57 ± 1.22 vs. 5.01 ± 0.95) are statistically different between groups, being higher in the Hast. In other domains, no significant differences were found. CONCLUSIONS: No difference between the effect of the abdominal hysterectomy on female sexual function in general was found, but better response was seen in the domains of orgasm and sexual satisfaction in women undergoing subtotal abdominal hysterectomy.